KAJIAN EKSPRESIF PADA MAKNA MAJAS METAFORA PADA PUISI - Ziyab Mahasin; Haidar Aziz (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This article discusses the meaning of figure of speech as outlined in a choice of words that is quite interesting and makes the reader curious about the meaning, also seen from the expressive approach that we can see from the author's point of view in making the poem. The purpose of making this article is to develop writing skills and increase students' and the public's interest in reading, as well as to describe the relationship or purpose of the author in conveying the poem "I Want Your Painting" to find the meaning contained in the poem with an expressive approach.